ANTAMA’ RI KARAENG PANGKALANG: (Budaya ziarah makam karaeng pangkalang oleh masyarakat islam lingkungan pangkalang kel. Canrego kec. Polongbangkeng selatan Kab. Takalar) - SYAFRIWANA, SYAFRIWANA (STAI YAPIS Takalar, 2021)
Abstract This research is a descriptive qualitative research, where the writing of this journal intends to write a history or culture that is still maintained by the community until now by writing the title